2019
DOI: 10.1007/s10815-019-01526-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of boar sperm functionality by the nitric oxide synthase/nitric oxide system

Abstract: Purpose Nitric oxide (NO) is a free radical synthesized mainly by nitric oxide synthases (NOSs). NO regulates many aspects in sperm physiology in different species. However, in vitro studies investigating NOS distribution, and how NO influences sperm capacitation and fertilization (IVF) in porcine, have been lacking. Therefore, our study aimed to clarify these aspects. Methods Two main experiments were conducted: (i) boar spermatozoa were capacitated in the presence/abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…Both signaling pathways, GSK-3α and PKA, are essential in the regulation of boar sperm motility [35][36][37]. Part of our results with ONOO − are in line with a recent study in boar spermatozoa that found that phosphorylation of PKA substrates is significantly lower when using NO synthase inhibitors [27]. The peroxynitrite-induced increase in GSK-3α phosphorylation is greater in TCM (2.4 fold-increase over control), than in TBM (1.7 fold-increase) as stimulating medium TCM alone is already promoting higher levels of phosphorylated GSK-3α than the un-stimulating TBM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both signaling pathways, GSK-3α and PKA, are essential in the regulation of boar sperm motility [35][36][37]. Part of our results with ONOO − are in line with a recent study in boar spermatozoa that found that phosphorylation of PKA substrates is significantly lower when using NO synthase inhibitors [27]. The peroxynitrite-induced increase in GSK-3α phosphorylation is greater in TCM (2.4 fold-increase over control), than in TBM (1.7 fold-increase) as stimulating medium TCM alone is already promoting higher levels of phosphorylated GSK-3α than the un-stimulating TBM.…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, in boar spermatozoa there are discrepancies regarding the involvement of NO pathway in the acrosome reaction. Thus, Staicu et al, (2019) [27] recently found that exogenous NO does not affect acrosome reaction, whereas Hou et al, (2008) [28] described that NO donor increases the number of acrosome-reacted spermatozoa. Our results with ONOO-support the idea that the pathway of NO, including related RNS, is not likely involved in the acrosome reaction of boar spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Meiser and Schulz [20] localized the nNOS isoform in the apical region of the head and tail of bull spermatozoa, whereas the eNOS was located only in the apical region. In ejaculated boar spermatozoa, eNOS and nNOS were identified in the acrosome and iNOS in the whole head, neck and flagellum [40]. However, no immunotypes or changes in NOS localization after in vitro capacitation were reported for bull or boar spermatozoa.…”
Section: Discussionmentioning
confidence: 91%
“…This behavior could be explained by the different roles of the NOS isoforms. Staicu et al [40] postulated that the constitutive isoforms (eNOS and nNOS) could be involved in sperm capacitation and that iNOS could be related to inflammation or stress, so the changes observed in iNOS during in vitro capacitation with melatonin could not exactly be related to this process. Taking into account the bimodal role that melatonin has on ram sperm in in vitro capacitation, stimulating this process at low concentrations (100 pM) and preventing it at high doses (1 µM) [27], it is quite surprising that both melatonin concentrations have similar effects on iNOS and nNOS distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is still unclear whether the physiological state (e.g., capacitation) of sperm cells may affect NOS distribution. In a recent study in capacitated boar spermatozoa, Staicu et al [23] found that the eNOS and nNOS are mainly distributed in the sperm head, whereas iNOS is localized in both the sperm head and the flagellum. The study also suggested a link between NOSs distribution and sperm normal function (capacitation, acrosome reaction, tyrosine phosphorylation, and Ca 2+ flux).…”
mentioning
confidence: 98%